Responses to an EIL-oriented General English Course: Views of Internal and External Stakeholders - Erbay Çetinkaya, Şakire; Kayaoğlu, Mustafa Naci (LPPM Universitas Advent Indonesia, 2024)
Teaching English as an International Language (TEIL) refers to teaching English as a truly international medium via exposing learners to diversity, adopting a broad culture view, fostering sensitivity and responsibility, being sensitive to local culture of learning, and equipping learners with communication strategies. To put this lately popular paradigm into actual teaching practice, a 10-week EIL-oriented General English course was devised for 53 English-majoring preparatory programme students at a public Turkish university as a part of a PhD study. The current report, as the qualitative part of that quasi-experimental PhD study, intended to evaluate the course with all its possible strengths, weaknesses, and ways to improve it for better future use based on both insider and outsider responses. While the data from internal stakeholders (N=25) were drawn from individual retrospective interviews, weekly written self-reports and a final open-ended questionnaire, the data from external ones (N=2) were gathered from peer classroom observation. The course appears to be a valuable experience as it increased learners’ world knowledge, enhanced their oral production in English, and provided an enjoyable and motivating atmosphere yet with some limitations regarding course content, materials and instructional choices. It is hoped that drawing such a field-tested picture will inspire others to make instructional decisions in line with the changing sociolinguistic landscape of English.